1998
DOI: 10.1046/j.1365-3180.1998.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of residue management and fallow length on weeds and rice yield

Abstract: Reduced fallow length in slash‐and‐burn rice (Oryza sativa L.) production systems of northern Laos increased weed pressure, labour requirement and the need for soil and moisture conservation. On‐farm and on‐station studies and on‐farm surveys were used to evaluate the effect of residue management and cropping intensity on weed population, rice yield and nematode density. Residue loads were 2.3–4.4 t ha−1 after a rice crop and 9.5 t ha−1 after 1 year of fallow. Compared with farmers' traditional burning of crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
1
17
1
1
Order By: Relevance
“…Toward the end of the 5-year experiment, during the growing season of the last crop, Ageratum conyzoides density was higher in CR than in the other treatments (Table 5). This supports earlier observations that there is a shift in weed populations toward A. conyzoides as cropping systems intensify (Roder et al 1998a). There were no differences between the treatments in soil inorganic N content at cutting time in 2003 and 2005 (Table 6).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Toward the end of the 5-year experiment, during the growing season of the last crop, Ageratum conyzoides density was higher in CR than in the other treatments (Table 5). This supports earlier observations that there is a shift in weed populations toward A. conyzoides as cropping systems intensify (Roder et al 1998a). There were no differences between the treatments in soil inorganic N content at cutting time in 2003 and 2005 (Table 6).…”
Section: Resultssupporting
confidence: 89%
“…In 2002, fallow periods of only 2 or 3 years were common (Troesch 2003). Increased cropping intensity has resulted in reduced soil fertility and rice yields, and increased problems from weeds and pests in northern Laos (Roder et al 1997a(Roder et al , b, 1998aSaito et al 2006a). …”
Section: Introductionmentioning
confidence: 99%
“…Burning of 15 cm deep rice hulls significantly reduce M. graminicola populations in the soil (Gergon et al, 2001). Compared with continuous rice treatments (averaged over burning and mulching treatments), treatments with fallow or cowpeas in the previous year had 32% less herbaceous weed biomass, 90% fewer A. conyzoides and over 99% fewer M. graminicola in field trials (Roder et al, 1998). In Philippines, rice based cropping sequences such as rice-mungbean, corncabbage rice, rice-tobacco-rice, ricewatermelon-rice, rice-cotton-rice, have been found effective in combating root-knot nematode menace in rice (Davide and Zorilla, 1983).…”
Section: Cultural Controlmentioning
confidence: 98%
“…The exact figures concerning the percent loss of yield are not framed, nonetheless, it is determined by the intensity capacity of weed. Roder et al (1998) have reported that yield of rice is negatively associated with the density of Ageratum [37]. Ageratum due to its heavy infestation intensity ruined the croplands of farmers of the lower Shivalik ranges of the Himalayas due to which farmers even abandoned their fields.…”
Section: Ageratum Conyzoides Lmentioning
confidence: 99%